I'm really stuck on this question, any help would be appreciated. If f(3)=-2 and f'(3)=5, find g'(3) if: g(x)=(3x^2)-5f(x) the answer is: -7 thanks in advance
Follow Math Help Forum on Facebook and Google+
Hey JellyOnion. Hint: Try differentiating g(x) by noting that d/dx(h(x) + j(x)) = h'(x) + j'(x) and substitute in f'(3) where appropriate.
Not sure i fully get what you mean chiro
g(x) = 3x^2 - 5 f(x) g'(x) = (3x^2 - 5 f(x)) ' g'(x) = (3x^2)' + (-5 f(x)) ' g'(x) = 3 * 2x + -5 * f ' (x) g'(x) = 6x - 5 f ' (x) Now set x = 3 g'(3) = 6*3 - 5 f ' (3) g'(3) = 18 - 5 * 5 g'(3) = 18 - 25 g'(3) = -7
Thanks mathguy25
View Tag Cloud